2016
DOI: 10.3803/enm.2016.31.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil, Perchlorate, and Thyroid-Stimulating Hormone Modulate High Concentrations of Iodide Instigated Mitochondrial Superoxide Production in the Thyroids of Metallothionein I/II Knockout Mice

Abstract: BackgroundIncreased oxidative stress has been suggested as one of the underlying mechanisms in iodide excess-induced thyroid disease. Metallothioneins (MTs) are regarded as scavengers of reactive oxygen species (ROS) in oxidative stress. Our aim is to investigate the effects of propylthiouracil (PTU), a thyroid peroxidase inhibitor, perchlorate (KClO4), a competitive inhibitor of iodide transport, and thyroid stimulating hormone (TSH) on mitochondrial superoxide production instigated by high concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Overexpression of MT in the human kidney reduced oxygen consumption, lowered cellular ATP levels, and decreased the oxidative phosphorylation capacity. 64,129 Metallothionein did not affect the number of mitochondria, but specifically reduced levels of cytochrome c oxidase subunit II proteins, which resulted in lower activity of Complex IV. 130 In addition, MT has been reported to inhibit superoxide generation and to dampen nitrosative damage, thereby preventing diabetes and its complications, including DCMP.…”
Section: Newly Proposed Mechanisms Of Action Of Mtmentioning
confidence: 98%
See 3 more Smart Citations
“…Overexpression of MT in the human kidney reduced oxygen consumption, lowered cellular ATP levels, and decreased the oxidative phosphorylation capacity. 64,129 Metallothionein did not affect the number of mitochondria, but specifically reduced levels of cytochrome c oxidase subunit II proteins, which resulted in lower activity of Complex IV. 130 In addition, MT has been reported to inhibit superoxide generation and to dampen nitrosative damage, thereby preventing diabetes and its complications, including DCMP.…”
Section: Newly Proposed Mechanisms Of Action Of Mtmentioning
confidence: 98%
“…Metallothionein also suppressed ischemia–reperfusion‐induced myocardial apoptosis mediated by mitochondrial dysfunction . In terms of the downstream signaling of ROS and RNS stimuli, intrinsic apoptotic signaling leads to mitochondrial membrane permeabilization and releases cytochrome c into the cytosol via the JNK signaling pathway …”
Section: Metallothionein and Its Broad‐spectrum Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also observed TSHR to be potent target for therapeutic study. A study done on PTU, KClO4, or TSH [87] revealed that these compounds reduced the oxidative stress due to high concentrations of iodide in the thyroids of both Metallothioneins(MTs) MT-I/II KO and WT mice. Bhabak and Mugesh in 2010 [88], and Manna, Roy and Mugesh in 2013 [89], reported Selenium analogues of ATDs to have better inhibitory effect compared to Sulphur based thinamide drugs on TPO suggesting that this selenium based drugs may be the next potential ATDs.…”
Section: Calculations Of Binding Free Energiesmentioning
confidence: 99%